Optical properties of linbo(3) single crystal grown by czochralski method - Sahar, Md. Rahim (American Institute of Physics, 2011)
Pure LiNbO3 single crystal was grown by Czochralski method using Automatic Diameter Control-Crystal Growth System (ADC-CGS). The transmission spectrum was determined by using Infrared Spectroscopy while the refractive index was determined using UV-Vis spectroscopy via the Sellmeier equation. The density was also measured using the Archimedes principle. It was found that the peak for the absorption vibrational spectrum for LiNbO3 crystal occurs at 801?cm-1, 672?cm-1, 639?cm-1 and 435?cm-1. The refractive index, ne was found to be 2.480 and the crystal density was around 4.64?g/cm3.